Islamic Educational Values in the Tradition of Almsgiving to Orphans in the Month of Muharram in Palembang City - Rosadahe, Lia Laili; Koswara, Ari; Wahyuni, Yulia; Oviyanti, Fitri; Maryamah, Maryamah (FKIP - Universitas Riau, 2025)
This study explores Islamic educational values in the tradition of charity for orphans during Muharram in Palembang City. The research aims to identify, analyse, and assess how these values are implemented and transmitted within the local community. This qualitative descriptive study involved purposive sampling of five mosques actively maintaining the tradition, employing data collection techniques including observation, in-depth interviews, and document analysis. Data were analyzed using the Miles and Huberman model. Findings reveal three primary value dimensions embedded in the tradition: faith-based values such as gratitude and divine accountability; social-moral values fostering compassion and dignity; and communal solidarity values reinforcing Islamic brotherhood and collective identity. The tradition operates as an effective informal educational platform, where participants internalize values through active engagement. The distinct participatory approaches notably facilitate confidence-building and sustained community integration. Conclusions emphasize the tradition’s role as a vital medium for moral, spiritual, and social education grounded in local culture. This research recommends strengthening informal community-based educational practices and incorporating intentional pedagogical elements into charitable programs. Policymakers should recognize informal religious education in access and quality assessments. Community leaders require pedagogical training to enhance educational effectiveness while preserving religious authenticity.